Acute Toxicity Tests of Alkaloid Pare (Momordica Charanthia) Fruit on The Histopathology of Liver - Wurlina, Wurlina; Meles, Dewa Ketut; Zakaria, Sunarni; Mustofa, Imam; Susilowati, Suherni; Adnyana, I Dewa Putu Anom (KnE Life Sciences, 2017)
Pare fruit (Momordica charanthia) potential as an antidiabetic. In preliminary research has proven that alkaloid of the Pare fruit (Momordica charanthia) can lower blood sugar levels of mice suffering from diabetes mellitus. Alkaloid Pare can improve pancreatic β-cell function by improving the preparation phase for the cell dividing (interphase) and repair the mitotic stages and increase the CDK expression in mice with diabetes mellitus. The purpose of this research was to determine the dose that causes the death of 50% (LD50) and to determine the toxicity effect of alkaloid Pare (Momordica charanthia) against damage in the form of congestion, degeneration, and necrosis of liver cells. Acute toxicity test with a 24-hour long treatment using 60 female mice, divided into six groups, each group consisted of 10 animals. The group is as follows: P0 only given distilled water, the group P1, P2, P3, P4 and P5 respectively treated 0.3 g/kg bw, 1 g/kg bw, 3 g/kg bw, 10 g/kg bw and 15 g/kg bw. Furthermore, all the mice were necropsied to take the liver for histopathology preparations to observe the occurrence of congestion, degeneration, and necrosis. The parameters observed through histopathological examination of the liver include congestion, degeneration, and necrosis. The results of the research tested by Kruskal-Wallis test with data obtained based on the value of scoring was not significantly different (α<0.05) in the liver histopathological changes in the form of congestion, degeneration, and necrosis between control and treatment groups orally in time 24 hours. The dose can cause 50% of deaths more than 15 g in mice are included in the category of medicinal substances which are not harmful. Keywords: Alkaloid Pare fruit, LD50, congestion, degeneration, necrosis, liver.